Initial experience with a newly developed cementless hip endoprosthesis - Hach, V.; Delfs, G. (Veterinary and Comparative Orthopaedics and Traumatology, 2009)
The HELICA-Endoprosthesis is a newly developed cementless hip prosthesis for dogs. It was implanted in 39 dogs that had severe hip osteoarthritis and a history of hip pain, as well as in one dog that had chronic hip luxation. One dog had a bilateral arthroplasty. The body weight of the patients ranged between 22 and 54 kg and their ages between nine months and 10 years. Both the femoral stem and acetabular component of the prosthesis were screwed into position following bony preparation. Additional fixation was not necessary as the components remain fixed in position until osteointegration is complete. There are currently five sizes of prosthesis available, and the various components such as the stem, cup and head are readily interchangeable. Although it appeared that good osseous anchorage of the prostheses in the bone on the surgery table had been obtained, three patients experienced both stem and cup loosening (one week, three weeks and six months after surgery). In one animal, stem loosening was observed six weeks after surgery, and another dog experienced a cup loosening two weeks postoperatively. Most of the complications were due to technical errors that occurred during the learning phase. Surgical revisions were successful in three out of five animals. In two animals we had to perform a femoral head and neck excision. Two other animals experienced radiographic bone resorption underneath the segmented collar of the femoral prosthesis but did not show any significant clinical signs of lameness. Another dog that showed signs of ischial neuropraxy after surgery, recovered completely within six weeks after surgery. All of the dogs were capable of weight bearing on the operated leg one day after surgery. The main advantage of the HELICA-Endoprosthesis is the relatively easy surgical technique and short surgery time. The initial clinical results in these 40 cases have been very encouraging. The aim of this study was to assess the early clinical results in these 39 dogs. Final evaluation can only be based on the results of gait analysis, long-term follow-up, and post mortem histological analysis.
Keywords: Total hip arthroplasty; dog; cementless; HELICA-prosthesis